Pennisetum pedicellatum as a short rotation forage crop for the eastern region of India - Chatterjee, B.N. (Journal of Soil and Water Conservation, 2022)
The paper summarises the results of work done in India on the role of a `all Grass' short ley of annual grass Pennisetum pedicellatutn during the period 1953 to 1970. Pennisetum Pedicellatum which out yields sorghum vulgare in green forage under similar management practices, can be easily cultivated by seed as a short rotation crop to fit in our crop sequences on uplands and medium lands. After hervest of green forage at ear emergence (80-90 days), the stubbles can be incorporated into the soil which add a good amount of organic matter to the soil. The organic matter thus added is easily rnineralisable and increases the subsequent crop yield even when the crop is not adequetly manured. Due to the improvement in soil structure brought about by growing the grass, under very intensive system of manuring and cropping, it helps in better utilization of added manure. The quality of the grass as a ley can still be improved if a suitable legume can be found out which can grow well in association with the grass.